A class of multiobjective control problems - de Oliveira, V. A.; Silva, Geraldo Nunes [UNESP]; Rojas-Medar, M. A. (John Wiley & Sons Ltd, 2009)
We introduce the class of MP-pseudoinvex multiobjective optimal control problems. We show that the concept of MP-pseudoinvexity is a sufficient condition of optimality and, further, that problems such that every control process satisfying Pontryagin's maximum principle is an optimal process are necessarily MP-pseudoinvex problems. Moreover, a sub-class of the MP-pseudoinvex problems, which we call MP-invex multiobjective optimal control problems, is defined. We prove that the set of optimal solutions of MP-invex multiobjective problems coincides with the set of optimal solutions of a related scalar problem. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: multiple objective programming; Control; Optimality conditions; generalized invexity